Land Use in the Rural-Urban Interface: Subdivision Design - Lauren McDonell; Martha C. Monroe; Jay Tomlinson (EDIS)
FOR-213, a 6-page illustrated fact sheet by Lauren McDonell, Martha C. Monroe, and Jay Tomlinson, describes new options for subdivision development and how citizens can help influence their local growth management and development plans by selecting opportunities that are appropriate for their area. Describes several exemplary Florida communities. Includes references. Published by the UF School of Forest Resources and Conservation, April 2009.